Taking the Good with the Bad–—Customer Type as a Segmentation Criterion and Differential Influencer of Sales Performance. Issue 3 (2nd July 2016) - Shannahan, Rachelle J.; Shannahan, Kirby L. J.; Bush, Alan J.; Moncrief, William C.
Abstract : The authors use the theory of organizing framework for sales research to demonstrate that customer organizational citizenship behavior (COCB) is a meaningful and useful customer segmentation criterion. First, they discern from open-ended responses what salespeople mean by "best, " "typical, " and "worst" customers. They then empirically demonstrate the differential influence of COCB by customer type on salespeople's evaluations of their customers and on three aspects of sales performance—customer-involved sales performance, salesperson behavioral effectiveness, and salesperson outcome productivity. The three customer-type comparison reveals that the COCB of best and typical customers has a positive influence on all three aspects of sales performance while the COCB of worst customers has a negative influence on them. These findings have implications for customer evaluation, customer segmentation, salesperson evaluation, and sales training.